2001
DOI: 10.1016/s0002-9440(10)63053-2
|View full text |Cite
|
Sign up to set email alerts
|

STK11/LKB1 Peutz-Jeghers Gene Inactivation in Intraductal Papillary-Mucinous Neoplasms of the Pancreas

Abstract: Intraductal papillary-mucinous neoplasms (IPMNs) of the pancreas are a distinct clinicopathological entity, characterized by dilated pancreatic ducts and ductules that are lined by papillary proliferations of tall columnar mucin-producing neoplastic epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
150
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(157 citation statements)
references
References 37 publications
3
150
0
4
Order By: Relevance
“…These genes were mutated in association with GNAS and/or KRAS mutations, with the exception of two IPMNs, one IPMN that only had a FGFR3 mutation and another that only had a TP53 mutation. Prior studies have reported STK11 mutations in a similar percentage of IPMNs (9%) [8]. Prior studies have found ATM and CDH1 somatic mutations in a small percentage of pancreatic ductal adenocarcinomas, but these mutations have not yet been reported in IPMNs [33,34].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These genes were mutated in association with GNAS and/or KRAS mutations, with the exception of two IPMNs, one IPMN that only had a FGFR3 mutation and another that only had a TP53 mutation. Prior studies have reported STK11 mutations in a similar percentage of IPMNs (9%) [8]. Prior studies have found ATM and CDH1 somatic mutations in a small percentage of pancreatic ductal adenocarcinomas, but these mutations have not yet been reported in IPMNs [33,34].…”
Section: Discussionmentioning
confidence: 98%
“…IPMNs commonly harbour activating mutations in KRAS and GNAS, and inactivating mutations in RNF43, CDKN2A/p16 and TP53, and less commonly mutations in BRAF, PIK3CA, STK11 and SMAD4 [5][6][7][8][9][10][11][12]. TP53, CDKN2A/p16 and SMAD4 mutations and/or loss of expression are generally found in higher-grade lesions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As a major upstream regulator of AMPactivated protein kinase subfamily members, including MARK/Par-1, LKB1 is involved in multiple aspects of cell function and has been linked to many human diseases especially malignant tumors. [63][64][65][66][67][68][69][70][71] Recently, LKB1 has been implicated in B-cell differentiation by mediating activation-induced cytidine deaminase-dependent remodeling of immunoglobulin genes, 72 as well as in T-cell differentiation by regulating TCR-mediated activation of phospholipase C gamma1 and AMP-activated protein kinase signaling. 73,74 LKB1 is directly phosphorylated by lymphocyte-specific protein tyrosine kinase and predominantly interacts with the adaptor protein LAT as well as phospholipase C gamma1 following TCR stimulation.…”
Section: Gck-iii Kinases As Immerging Novel Immune Regulatorsmentioning
confidence: 99%
“…A markedly increased incidence of carcinomas of the gastrointestinal tract including stomach, small bowel, colon and pancreatic cancer, as well as breast, ovary, uterus, cervix, lung and testis cancer has been observed through longitudinal studies of affected kindreds (Giardiello et al, 1987(Giardiello et al, , 2000Spigelman et al, 1989;Gruber et al, 1998;Lim et al, 2004;Hearle et al, 2006). In addition, rare tumors have been associated with PJS including those of a reproductive origin-including testicular and ovarian sex cord tumors, Sertoli cell tumors and adenoma malignum of the cervix-as well as non-adenocarcinoma pancreatic tumors, including pancreatic intraductal papillary mucinous neoplasia and serous cystadenomas (Podczaski et al, 1991;Young et al, 1995;Tomlinson and Houlston, 1997;Su et al, 1999;Sato et al, 2001;Yee et al, 2003).…”
Section: Peutz-jeghers Syndrome and Human Cancer Geneticsmentioning
confidence: 99%